2013
DOI: 10.5888/pcd10.120324
|View full text |Cite
|
Sign up to set email alerts
|

Use and Effectiveness of Quitlines for Smokers With Diabetes: Cessation and Weight Outcomes, Washington State Tobacco Quit Line, 2008

Abstract: IntroductionHaving diabetes and smoking increases the risk of morbidity and mortality. However, cessation-related weight gain, a common side effect during quitting, can further complicate diabetes. Evidence-based telephone quitlines can support quitting but have not been studied adequately in populations with chronic diseases such as diabetes. The purpose of this study was to evaluate the use and effectiveness of a tobacco quitline among tobacco users with diabetes. Cessationrelated weight concerns and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…In a cross-sectional study of smokers who enrolled in a state quitline, Schauer et al found that having diabetes had no impact on the effectiveness of smoking cessation treatment; 24.3% of those with diabetes versus 22.5% of those without diabetes quit smoking at 6 months and no significant differences existed between groups for weight gain, regardless of quit status. However, participants with diabetes reported more weight gain in previous quit attempts; 34.2% of those with diabetes vs. 22.4% of those without diabetes gained >20 lbs (8.84 kg) (P 5 0.03) (96). By contrast, an earlier study evaluated 6-month cessation outcomes of state quitlines by chronic disease and reported that those with diabetes had lower quit rates than those who did not have diabetes (97).…”
Section: Tobacco Cessation and Weight Management Combined Interventiomentioning
confidence: 86%
“…In a cross-sectional study of smokers who enrolled in a state quitline, Schauer et al found that having diabetes had no impact on the effectiveness of smoking cessation treatment; 24.3% of those with diabetes versus 22.5% of those without diabetes quit smoking at 6 months and no significant differences existed between groups for weight gain, regardless of quit status. However, participants with diabetes reported more weight gain in previous quit attempts; 34.2% of those with diabetes vs. 22.4% of those without diabetes gained >20 lbs (8.84 kg) (P 5 0.03) (96). By contrast, an earlier study evaluated 6-month cessation outcomes of state quitlines by chronic disease and reported that those with diabetes had lower quit rates than those who did not have diabetes (97).…”
Section: Tobacco Cessation and Weight Management Combined Interventiomentioning
confidence: 86%
“…In general, the results supported all four aims. The fact these aims were achieved in an uninsured sample of smokers is encouraging because they are a generally challenging population to engage in research (e.g., low retention) and tend to have worse treatment outcomes than the insured (Bush et al, 2012;Schauer et al, 2013;Stead et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The data collection protocol yielded overall retention rates that were higher than the 55% average rates for comparable general population telephone-delivered smoking cessation interventions (Bush et al, 2012;Schauer et al, 2013;Stead et al, 2013). Finally, the per-protocol implementation data demonstrated that ACT can be implemented with a QL population with high and similar competence as CBT.…”
Section: Design Feasibilitymentioning
confidence: 95%
“…The results of quitline studies have been more promising. Tobacco users with diabetes used the quitline in greater proportion than they were represented in the general population, and had quit rates that were comparable with quitline users without diabetes. More studies are required to understand the best behavioral interventions for smokers with diabetes.…”
Section: Discussionmentioning
confidence: 99%